Explore Westonci.ca, the top Q&A platform where your questions are answered by professionals and enthusiasts alike. Join our Q&A platform to connect with experts dedicated to providing precise answers to your questions in different areas. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform.
Sagot :
Answer:
The results of the y variable using the function rule y = -2x + 3 are:
- x y
- -4 11
- -2 7
- 0 3
- 2 -1
Step-by-step explanation:
To obtain each result of the answer, you must to use the function rule:
- y = -2x + 3
And replace the X variable by the number in the same row. Now, we're gonna see the calculations one by one.
When x is -4:
- y = -2(-4) + 3
- y = 8 + 3
- y = 11
When x is -2
- y = -2(-2) + 3
- y = 4 + 3
- y = 7
When x is 0:
- y = -2(0) + 3
- y = 0 + 3
- y = 3
When x is 2:
- y = -2(2) + 3
- y = -4 + 3
- y = -1
In this form, the results are 11, 7, 3, and -1 respectively.
Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. We hope this was helpful. Please come back whenever you need more information or answers to your queries. Westonci.ca is here to provide the answers you seek. Return often for more expert solutions.